Answer:
![f(x) = (x + 1)(x - 7)](https://img.qammunity.org/2021/formulas/mathematics/high-school/1raajn8vgekrfsilny5g5tl698as8frcf7.png)
Explanation:
For a quadratic function to have a vertex with an x-coordinate of 3, then
![3 = - (b)/(2a)](https://img.qammunity.org/2021/formulas/mathematics/high-school/i8s4hvmwqx8jt95m05movfnbe8vlfmbkkj.png)
Let a=1, then we have
![3 = - (b)/(2)](https://img.qammunity.org/2021/formulas/mathematics/high-school/30gdbjtlq5xzvl85bch86yfuo19fcsaio8.png)
![b = - 2 * 3 = - 6](https://img.qammunity.org/2021/formulas/mathematics/high-school/oylkj2mnomdvb66caxe70ap2308g3tpfxg.png)
So now our equation becomes:
![f(x) = {x}^(2) - 6x + c](https://img.qammunity.org/2021/formulas/mathematics/high-school/5ijjx5kt57ihwnjendw6gwndtvru7ta3dz.png)
We now find two factors of c that add up to -6.
Let these factors be 1, and c.
Then
![c + 1 = - 6](https://img.qammunity.org/2021/formulas/mathematics/high-school/jk4ky2vv52bnnpv194stex72tfyt4b0uak.png)
![c = - 6 - 1 = - 7](https://img.qammunity.org/2021/formulas/mathematics/high-school/wwxlf448z9bamtbyxykvho54w9x3f8h5l2.png)
Therefore the factors are :
1 and -7.
The function becomes:
![f(x) = {x}^(2) - 6x - 7](https://img.qammunity.org/2021/formulas/mathematics/high-school/bkunv2dpjx3p5jkf51286xmdmi7cwvqsqw.png)
The factored form is
![f(x) = (x + 1)(x - 7)](https://img.qammunity.org/2021/formulas/mathematics/high-school/1raajn8vgekrfsilny5g5tl698as8frcf7.png)